Pengaruh Beban Kerja Fisik terhadap Tingkat Disabilitas Pasien Nyeri Punggung Bawah di RSD dr. Soebandi Jember (Influence of Workload Level on Low Back Pain Patient’s Physical Disabilities at RSD dr. Soebandi Jember) - Imam Adi Nugroho; Ancah Caesarina Novi Marchianti; Yuli Hermansyah (UPT Percetakan dan Penerbitan Universitas Jember, 2017)
Disability is a condition that the patient loss of opportunities to take a part in normal life due to physical, mental and social barrier. Disability is commonly caused by low back pain. Physical workload is the one of risk factors of low back pain. The purpose of study was to measure the influence of physical workload and disability caused by low back pain at RSD dr. Soebandi Jember. This research was analytic observational study with cross sectional approach. Physical workload was measured by Self Measured Quistionere Physical Demand and disability was measured by Oswestry Disability Index. Physical workload was divided into manual handling and work postures. As many as 32 samples were collected during May-June 2016. The data were analyzed by Spearman correlations test and showed there were no significantly influence between manual handling (α=0,769), work postures (α=0.763) and disability. Spearman correlation test also showed there were no relationship between manual handling (r=0,055), work postures (r=-0,054) and disability. Thus it, can be concluded that there were no influence between physical workload and disability caused by low back pain in RSD dr. Soebandi Jember. Keywords: Low back pain, physical workload, disability